Ambiguous contagion the discourse of race in South African English writing, 1890-1930 - Cornwell, David Gareth Napier (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1996)
This study explores representations of race and racial difference in the writing of white South Africans in English, between the years, approximately, of 1890 and 1930. The first chapter essays a theoretical and historical investigation of the concept of race and offers a narrative of the rise of Western racialism. Its conclusion, that race has functioned as a vehicle of displacement for other forms of difference in the competition for advantage among social groups, is qualified in Chapter Two by the postulate of an anthropologial absolute, the "ethnic imperative", to help account for the strategic emergence of racialism in specific historical circumstances. The role of the ethnic imperative in the moral economy of colonial South Africa in the years 1890-1930 is examined through the analysis of three representative texts. In Chapter Three, a wide range of primary material is canvassed for prevailing views on the "Native Question", the perceived social threat posed by the half-caste, and the "Black Peril", culminating in the detailed examination of a fictional text. A particular concern in both Chapters Two and Three is the imagery of disease and contagion in terms of which racial contact is typically represented. The following chapter situates the literary works discussed in the study in the context of the South African literary tradition, then uses the example of selected short stories to indicate some narratological problems encountered by the writer with a racialist agenda within the medium of realist fiction. Chapters Five and Six investigate, through the close reading of selected novels, thematic concerns rooted in the intersection of the discourse of race with those of gender and social class. The final chapter reveals how William Plomer's novel, Turbott Wolfe, represents a volatile synthesis of a standard discourse on social class, an acknowledgement of the ethnic imperative, the imagery of contagion, and a principled repudiation of racialism, in a multi-faceted, modernist, and partially self-aware fashion. The more salient conclusions reached by this study concern the inadequacy of purely materialist analysis to account for the phenomenon of racialism, the historically determined link between racial attitudes and sexuality, and the manifest incompatibility of racial ideology with the liberal humanism inscribed in the formal requirements of the realist work of fiction.
Keywords: South African literature -- History and criticism; Race in literature; Social classes in literature; Ethnicity in literature; Sex role in literature; Race relations in literature